Assessing the extent and public health impact of bat predation by domestic animals using data from a rabies passive surveillance program - Amy G. Wilson; Christine Fehlner-Gardiner; Scott Wilson; Karra N. Pierce; Glenna F. McGregor; Catalina González; Tanya M. J. Luszcz (Public Library of Science (PLoS), 2022)
Domestic animals can serve as consequential conveyors of zoonotic pathogens across wildlife-human interfaces. Still, there has been little study on how different domestic species and their behaviors influence the zoonotic risk to humans. In this study, we examined patterns of bat encounters with domestic animals that resulted in submission for testing at the rabies laboratories of the Canadian Food Inspection Agency (CFIA) during 2014-2020. Our goals were specifically to examine how the number of bats submitted and the number of rabies positive bats varied by the type of domestic animal exposure and whether domestic cats were indoor or free-roaming. The CFIA reported 6258 bat submissions for rabies testing, of which 41.5% and 8.7% had encounter histories with cats and dogs, respectively. A much smaller fraction of bat submissions (0.3%) had exposure to other domestic animals, and 49.5% had no domestic animal exposure. For the bat submissions related to cats, and where lifestyle was noted, 91.1% were associated with free-roaming cats and 8.9% with indoor cats. Model results indicated the probability of a rabies-positive bat was the highest with a history of dog association (20.2%), followed by bats with no animal exposure (16.7%), free-roaming cats (6.9%), cats with unspecified histories (6.0%) and the lowest probability associated with non-free-roaming (indoor) cats (3.8%). Although there was lower rabies prevalence in bats associated with cats compared to dogs, the 4.8 fold higher number of cat-bat interactions cumulatively leads to a greater overall rabies exposure risk to humans from any free-roaming outdoor cats. This study suggests that free-roaming owned cats may have an underappreciated role in cryptic rabies exposures in humans and as a significant predator of bats. Preventing free-roaming in cats is a cost-effective and underutilized public health recommendation for rabies prevention that also synergistically reduces the health burden of other feline-associated zoonotic diseases and promotes feline welfare and wildlife conservation.